Reflections on student agency through the use of voice notes in university English tutorials during Covid-19 - Motala, Atiyyah; Kajee, Leila (Journal for Language Teaching, 2025)
Higher Education Institutions (HEIs) have had to reconsider and reshape their teaching and learning pedagogies overnight during the Covid-19 pandemic. The dramatic closure of education institutions in South Africa, and worldwide, gave rise to questions around our adaptability, readiness, and response to change in the HEI sector. While universities made the rapid move to emergency remote teaching and learning, it remained to be seen how students responded to this move. This study reports on the use of voice notes to promote student voice and agency in English tutorials at a university in Gauteng, South Africa. The main aim of this paper is to examine student reflections on the use of voice notes to foster agency in tutorials. Based on the inequalities present in South Africa’s education system, specifically HEIs, this paper is conceptually framed in critical theory. Through an examination of data elicited from student interviews, observations, and voice notes, this case study finds that participant reflections highlight the significance of a critical approach, in utilising voice notes in English tutorials, to assist students in being active participants in the teaching and learning process.